Hypertrophic cardiomyopathy unveiling multiple myeloma: A diagnostic challenge - Lamassab Nour el houda; Bilal Marwa; Noha El ouafi; Nabila Ismaili (Radiology Case Reports)
Hypertrophic cardiomyopathy can be a rare initial presentation of hematologic malignancies such as multiple myeloma that is caused by an uncontrolled clonal proliferation of plasma cells. We report a case of a 65-year-old man, presenting with congestive heart failure, in whom EKJ and echocardiography findings are suggestive of cardiac amyloidosis, and which the etiological assessment identified multiple myeloma as the underlying cause. Through this case, we demonstrate that cardiac amyloidosis secondary to multiple myeloma can present as a newly diagnosed and rapidly progressive heart failure before any typical clinical features of multiple myeloma appear.